DEVELOPMENT AND VALIDATION OF FOUR-TIER DIAGNOSTICS INSTRUMENT FOR CHEMICAL EQUILIBRIUM - Nuchrurita Rosida; Hayuni Retno Widarti; Rizki Amelia (Prodi Pendidikan IPA FMIPA Universitas Negeri Malang, 2021)
Misconceptions can affect students' understanding. Identifying misconceptions is an important first step in gaining an understanding of student learning. One of the instruments that can be used to diagnose student misconceptions is a four-tier diagnostic instrument. This study aims to develop a four-tier diagnostic instrument on the material of chemical equilibrium. This research is a research and development (RnD) research. The research stages consisted of: concept mapping, pre-test, identification of unscientific student concepts, developing prototypes, validating prototypes, and completing the final prototype. The product development stages consist of: analysis of learning tools, preparation of test question grids, writing of items, as well as reviewing and revising questions. The data analysis carried out included validity, reliability, difficulty level, and distractor effectiveness. The final product that is produced consists of 20 items on the sub-topic of dynamic equilibrium, equilibrium constant, and equilibrium shift. The results of content validation on two expert lecturers found that the four-tier diagnostic instrument on chemical equilibrium material was valid and suitable for use. In empirical validation, it was found that 3 items were invalid. The resulting test questions are reliable with a reliability score of 0.77. In general, this four-tier diagnostic instrument is at a moderate level and is an effective distractor. This shows that a four-tier diagnostic instrument on chemical equilibrium material can be used to diagnose student misconceptions.